Fatal toxic shock syndrome following tattooing - Schreiner, Kristin; Balikowski, Marek (Forensic science, medicine, and pathology, 2025)
Toxic shock syndrome (TSS) is a rare but potentially fatal condition caused by toxin-producing strains of Staphylococcus aureus. While typically associated with menstruation or postoperative complications, non-menstrual forms related to skin trauma, including tattooing, are increasingly recognized.